Peran Kepuasan Imbalan, Persepsi Beban Kerja, Keseimbangan Kerja/Kehidupan Terhadap Retensi Karyawan - Shidiq, Idhar; Parahyanti, Endang (Syntax Corporation, 2025)
Employee retention programs are among the strategies that organizations can employ to ensure employees remain within the organization to support the achievement of organizational goals. These efforts include strategies and actions designed to keep employees motivated, satisfied, and loyal. Effective retention is essential for maintaining organizational stability and reducing costs associated with employee turnover. This study aimed to examine the relationship between pay satisfaction, perceived workload, and work-life balance with employee retention at RSUA, a public healthcare organization. The population consisted of 309 employees, with a sample of 123 participants selected using a convenience sampling technique. Statistical analysis using Pearson’s correlation revealed no significant relationship between pay satisfaction and work-life balance with employee retention. However, perceived workload was found to have a positive and significant relationship with employee retention (r = 0.257, p < .05). Based on these findings, it is recommended that RSUA prioritize managing employee workload at a level that is challenging but not excessive. Furthermore, the organization should promote job crafting, particularly through increasing challenging job demands, to maintain positive perceptions of workload as a core element in employee retention strategies. Overall, employee retention efforts may be more effective when focused on managing meaningful and balanced workloads rather than relying solely on financial incentives or general work-life balance programs.